THE INFLUENCE OF PARAMETERS OF THE PERTURBED IONOSPHERE TO THE ERROR TRACKING PHASE OF NAVIGATION RADIOSIGNAL - Konstantin Alexandrovich Katkov; Vladimir Petrovich Pashintsev; Yevgeny Konstantinovich Katkov (Современная наука и инновации)
The paper considers the impact of ionospheric nonuniformities on the characteristics of the tracking phase of navigation equipment of consumers of satellite radio navigation systems. The contribution of thermal noise of the receiver and the phase fluctuations of the signal to the error tracking phase were estimated.